Peripheral nerve injuries in children: prevalence, mechanisms and concomitant injuries : a major trauma center’s experience - Aman, Martin; Zimmermann, Kim S.; Böcker, Arne Hendrik; Thielen, Mirjam; Falkner, Florian; Däschler, Simeon C.; Stolle, Annette M.; Kneser, Ulrich; Harhaus-Wähner, Leila (European journal of medical research, 2023)
Peripheral nerve injuries are severe conditions with potential lifelong impairment, which is especially meaningful for the pediatric population. Knowledge on prevalence, injury mechanisms and concomitant injuries is, therefore, of utmost importance to increase clinician awareness and enable early diagnosis and treatment. As current literature on pediatric nerve lesions and concomitant injuries is scarce, we aimed to analyze all details of our patient population.